On IoT applications: a proposed SDP framework for MQTT. Issue 22 (1st October 2019) - Refaey, A.; Sallam, A.; Shami, A.
Abstract : In this work, the software‐defined perimeter (SDP) is considered for the Message Queuing Telemetry Transport (MQTT) protocol framework in the Internet of Things (IoT) applications. In fact, the SDP provides an additional layer of security with or without SSL/TLS by replacing the traditional login method (username/password) with a single‐packet authorisation (SPA) process. This will blacken the end devices, by cloaking and causing them to be inaccessible by attackers. Consequently, this prevents the log‐in information from being compromised in the absence of encryption. Eventually, the framework is evaluated through an implementation testbed and system proved to be secure against denial of service active and off‐line dictionary types of attacks, even with the use of weak login credentials. All the while, achieving measurable efficiency over the traditional use of MQTT.